Ladislaus von Bortkiewicz. The theory of population and moral statistics according to W. Lexis - Sheynin, Oscar (Silesian Statistical Review, 2019)
W. Lexis founded the continental direction of statistics which the Biometric school largely ignored. Bortkiewicz described his work but mostly without providing exact references. He criticized Lexis for paying too much attention to philosophical problems but mentioned Lexis’ merits: a test for the stability of statistical series (only much later rejected by Chuprov), the study of mortality and sex ratio at birth; the application of the law of large numbers. Lexis, as Bortkiewicz concluded, essentially contributed to the general theory of statistics
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2019, Nr 17 (23), s. 85-109
Keywords: law of large numbers; mortality; stability of statistical series